US healthcare international comparisons: what are we comparing?. (8th August 2019) - Jordan, David W.; Boucher, David
International comparisons between the US quasi-market and other nations' nationalised healthcare or insurance models have, and continue to generate significant debate. Discussions inevitably cite the World Health Organization's or Commonwealth Fund's work, but what these comparisons actually examine is somewhat unclear when examining the complexity of what is being compared. Often international healthcare comparisons are presented as one based on the quality of healthcare in subject national systems. This paper discusses some of the complexities associated with international comparisons, provides some additional perspectives for metrics often cited in international comparisons, and suggests we may be served better by adjusting the premises of continued discourse in the matter. If the purpose of international comparisons is to evaluate the world laboratory of healthcare policy and processes, which it should, this paper suggests the discussion needs redirected in both focus and content.